РОЛЬ КУЛЬТУРНОГО НАСЛЕДИЯ В ФОРМИРОВАНИИ СОВРЕМЕННОГО РОМАННОГО ЖАНРА В ТУНИСЕ - Надирова, Г. Е. (Journal of Oriental Studies, 2016)
The novel as a genre has occupied a prominent position in the Arabic-language Tunisian literature since its independence. The century-longprocess shows that the Tunisian novel is a live artistic organism open to external influences and itself influencing the society and art. "Intellectual novels", which try to assess the present while activelyusing elements of artistic legacy, play an important role within the genre. At the form level a constant process of search and change goes on which leads to unexpected and interesting results such as novel-play where narrative is added drama resulting in a new original genre, new literary form.